2020
DOI: 10.1002/advs.202000749
|View full text |Cite
|
Sign up to set email alerts
|

Sequence‐Defined Peptoids with OH and COOH Groups As Binders to Reduce Cracks of Si Nanoparticles of Lithium‐Ion Batteries

Abstract: Silicone (Si) is one type of anode materials with intriguingly high theoretical capacity. However, the severe volume change associated with the repeated lithiation and delithiation processes hampers the mechanical/electrical integrity of Si anodes and hence reduces the battery's cycle‐life. To address this issue, sequence‐defined peptoids are designed and fabricated with two tailored functional groups, “OH” and “COOH”, as cross‐linkable polymeric binders for Si anodes of LIBs. Experimental results show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 72 publications
0
34
0
Order By: Relevance
“…To make better use of the advantages of –COOH and –OH, Zhang et al fabricated a sequence‐defined peptoids (P1) with programmed –COOH and –OH groups on the chain as a crosslinkable binder for SiNP anodes (Figure 7B). 106 The results showed that SiNP anodes with P1 binder showed excellent cycling performance (~3110 mA h g −1 after 500 cycles at 1.0 A g −1 ) and good rate capability (1328.2 mA h g −1 even at 7 C), compared with CMC or P2 (substituting the –OH groups in P1 by –OCH 3 groups) binders (Figure 7C). Mussel‐inspired polymer binders have attracted a lot of research interests due to the excellent adhesion by the catechol groups 107‐110 .…”
Section: Designing Of Polymer Binders For Si‐based Anodesmentioning
confidence: 97%
See 4 more Smart Citations
“…To make better use of the advantages of –COOH and –OH, Zhang et al fabricated a sequence‐defined peptoids (P1) with programmed –COOH and –OH groups on the chain as a crosslinkable binder for SiNP anodes (Figure 7B). 106 The results showed that SiNP anodes with P1 binder showed excellent cycling performance (~3110 mA h g −1 after 500 cycles at 1.0 A g −1 ) and good rate capability (1328.2 mA h g −1 even at 7 C), compared with CMC or P2 (substituting the –OH groups in P1 by –OCH 3 groups) binders (Figure 7C). Mussel‐inspired polymer binders have attracted a lot of research interests due to the excellent adhesion by the catechol groups 107‐110 .…”
Section: Designing Of Polymer Binders For Si‐based Anodesmentioning
confidence: 97%
“…(A) Chemical structure of poly(vinyl alcohol) (PVA). (B) Chemical structure of peptoids (P1) 106 . Copyright 2020, Wiley‐VCH.…”
Section: Designing Of Polymer Binders For Si‐based Anodesmentioning
confidence: 99%
See 3 more Smart Citations